Die etymologische Exegese des Namens »Manasse« in der Patristik und bei einigen Authorn des frühen Mittelalters - Kranz LC, Dirk Kurt (Alpha Omega, 2010)
This essay approaches a theme of particular interest for biblical scholars: patristic etymological exegesis, a way of interpreting the spiritual meaning of persons and places that was very common in the patristic era. In the first place I will expound the methodological questions involved in such an exegesis; in a second moment the patristic productions as much as collections and compilations, called onomastica, will be summarily presented. Finally it will be shown how the Fathers interpreted the name Manasseh from this methodological point of view in their biblical exegesis.